Dejavniki, ki vplivajo na pogostost in višino prejete napitnine: analiza predhodnih raziskav - Raspor, Andrej (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The starting point of this article was to gather the studies regarding the factors that address the impact on tipping fees from different perspectives. The main goal of the research presented was to group factors affecting the tipping fees and thus facilitate further researches and verification of factors in practice. Following scientific methods were used in this article, (1) theoretical studies, and (2) case studies. On the basis of the studies presented groups of factors that affect tipping fees were formed. Our guiding premise was the following question: could the factors affecting tipping fees in the field of hospitality industry be differentiated from those affecting tipping fees in the gambling industry? It can be therefore concluded that there are certain specifics found within the fields mentioned but basical division of groups of factors is similar for both. The factors under question are thus in the fields of hospitality and gaming industry mutually comparable, while also providing useful grounds for other service activities.
Keywords: tips; employees; hosts; gaming industry; hospitality industry